Week 144 Resistance Analysis of Elvitegravir/Cobicistat/Emtricitabine/Tenofovir DF versus Efavirenz/Emtricitabine/Tenofovir DF in Antiretroviral-Naive Patients. Issue 3 (April 2015) - White, Kirsten L; Kulkarni, Rima; McColl, Damian J; Rhee, Martin S; Szwarcberg, Javier; Cheng, Andrew K; Miller, Michael D
Background: Here, the baseline and emergent resistance to elvitegravir/cobicistat/emtricitabine/tenofovir disoproxil fumarate (EVG/COBI/FTC/TDF) versus efavirenz (EFV)/FTC/TDF in HIV-1-infected antiretroviral-naive adults through 144 weeks from the randomized, ongoing, Phase III study GS-US-236-0102 is described. Methods: HIV-1 protease (PR) and reverse transcriptase (RT) were sequenced at screening; patients with HIV-1 resistant to EFV, FTC or TDF were excluded. Genotypic/phenotypic analyses were performed at virological failure confirmation and baseline for PR, RT and integrase (IN) for patients with virological failure and for patients with HIV-1 RNA≥400 copies/ml at weeks 48, 96, 144 or early study drug discontinuation. Retrospective, baseline, IN genotyping was conducted for EVG/COBI/FTC/ TDF patients. Results: In the EVG/COBI/FTC/TDF group through week 144, HIV-1 from 10 patients (2.9%; 10/348 treated patients) developed primary IN strand transfer inhibitor ( n =9) and/or nucleoside RT inhibitor resistance substitutions ( n =10). The emergence of resistance decreased over time with 8, 2 and 0 patients developing HIV-1 resistance through week 48, post-week 48–96 and post-week 96–144, respectively. Emergent substitutions were E92Q ( n =7), N155H ( n =3), Q148R ( n =1) and T66I ( n =1) in IN, and M184V/I ( n =10) and K65R ( n =4) in RT. All 10 isolates had reduced susceptibility to EVG, FTC or TDF. Virus with EVG phenotypic resistance had cross-resistance to raltegravir. In the EFV/ FTC/TDF group, virus from 14 patients (4.0%; 14/352 treated patients; 4 during weeks 96–144) developed a resistance substitution to EFV ( n =14; K103N: n =13), FTC (M184V/I: n =4) or TDF (K65R: n =3). Conclusions: Resistance development to EVG/COBI/FTC/ TDF was infrequent through 144 weeks of therapy and decreased over time, consistent with durable efficacy.